129k views
2 votes
How do I make 4(x+3)=3(3x-1) into a simpler form without parentheses. Then substitute 3 for x.

User Epoch
by
5.0k points

2 Answers

5 votes

Answer:

x=3

Explanation:

1) Expand.

4x+12=9x-34x+12=9x−3

2) Subtract 4x4x from both sides.

12=9x-3-4x12=9x−3−4x

3) Simplify 9x-3-4x9x−3−4x to 5x-35x−3.

12=5x-312=5x−3

4) Add 33 to both sides.

12+3=5x12+3=5x

5) Simplify 12+312+3 to 1515.

15=5x15=5x

6) Divide both sides by 55.

\frac{15}{5}=x

​5

)

​15

​​ =x

7) Simplify \frac{15}{5}

​5

​15

​​ to 33.

3=x3=x

8) Switch sides.

x=3

User AshB
by
5.5k points
4 votes
4x+12=9x-3
12+12=27-3
24=24
User Mmurphy
by
5.0k points